The role of achievement motivation on the interlanguage fossilization of middle-aged English-as-a-second-language learners - Vujisic, Zoran (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2007)
Second language acquisition (SLA) is seldom entirely successful with adult learners. It has been suggested that all second language (L2) learners, in the process of mastering a target language (TL), develop a linguistic system that is self-contained and different from both the learner's native language and the TL. This system is referred to as 'interlanguage' (lL). In the process of SLA, IL evolves into an ever-closer approximation of the TL, and ideally, a learner's IL should continue to advance until it becomes equivalent to the TL. However, it has been observed that somewhere in the L2 learning process, IL may reach one or more plateaus during which the development of the IL is delayed or arrested. A permanent cessation of progress toward the TL is referred to as 'fossilization'. Researchers in SLA agree that motivation is one of the key factors influencing language-learning success and studies suggest that some language learning motivation may be related to the need for achievement. The purpose of this research was to establish if adult ESL learners are aware of fossilization and, to examine if motivation, and more specifically achievement motivation, is a factor in IL fossilization. The participants in this study consisted of 15 ESL learners in Puerto Rico who had at least eight years of formal ESL training. The instrument used to gather information included a questionnaire to obtain demographical and qualifying data, an 'English Language Proficiency Evaluation' to determine levels of IL fossilization, a 'Measure of Achievement Motivation' to ascertain achievement motive, and individual and group interviews in order to ascertain perception(s) regarding the role of motivation on fossilization and perceptions regarding the barriers to achieving TL competency. The research demonstrated that there is a moderate to strong positive relationship between IL fossilization and achievement motivation, i.e., high achievement motive is correlated to TL competency and descending levels of achievement motive are correlated to ascending levels of IL fossilization. The findings have significant implications for both ESL learning and instruction, and suggest that not all IL fossilization may be permanent.
Keywords: Second language acquisition; Language and languages -- Study and teaching; Fossilization (Linguistics); Interlanguage (Language learning); nglish language -- Study and teaching -- Foreign speakers; Motivation in education